Ten years with colistin: a retrospective case series. Issue 9 (13th June 2016) - Katz, D. E.; Marchaim, D.; Assous, M. V.; Yinnon, A.; Wiener‐Well, Y.; Ben‐Chetrit, E.
Summary: Objective: At the Shaare Zedek Medical Center, we have been using colistimethate sodium (CMS) for empiric as well as pathogen‐directed treatment. We present our 10‐year experience. Methods: We conducted a retrospective case‐series analysis of patients admitted from 1 January 2004 through 1 May 2014 who received at least one dose of CMS. Patient characteristics analysed for all admission for which patients received CMS, included: age, number of re‐admissions, admission ward, renal function, disposition and microbiology results. Overall trend in defined daily dose (DDD) for CMS and resistant isolates was analysed. Results: A total of 5603 admissions met inclusion criteria. Patients' mean (±SD) age was 80 ± 14 years, 1162 (48%) of the admissions were from a healthcare facility and 4367 (78%) of the admissions were to general Internal Medicine wards. The median number of hospital admissions per patient was 5, median admission and discharge creatinine (mg/dl) were 1.05 and 1.01, respectively; 2.3% of admissions required first‐time dialysis. The discharge rate from the hospital was 58.4%. Excluding intrinsically CMS‐resistant gram‐negative organisms, bloodstream and urine isolates were 98% and 100% susceptible, respectively. CMS use (DDDs) increased during the study (p for trend = 0.04) without significant increase in incidence of multidrug‐resistant organisms. Conclusions: Colistimethate sodium use at our institution has increased during this 10‐year period. Nevertheless, there is no increasing trend in CMS‐resistant organisms, 58% of the patients were discharged alive, and we did not observe significant nephrotoxicity in patients prescribed CMS. CMS should be reserved for microbiologically confirmed extensively drug‐resistant gram‐negative infections.